PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KYAI TERHADAP PENINGKATAN JUMLAH SANTRI MELALUI PROFESIONALISME GURU DI PP IHYAUL QUR’AN NURURRAHMAN WAGIR MALANG - Wicaksono Amhar Galih; Mohammad Asrori; Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Kyai are not only required to maintain Islamic boarding school traditions, but also must be able to innovate so that Islamic boarding schools remain relevant with current developments. Teacher professionalism is also a crucial factor in improving the quality of education in Islamic boarding schools. Teachers who are competent and have high dedication will be able to produce graduates who not only master religious knowledge, but also have the skills needed in the world of work. Apart from that, an increase in the number of students is an indicator of the success of an Islamic boarding school. The approach in this research uses a quantitative approach with a correlational research type. The aim of this research is will analyze the influence of the kyai's transformational leadership style on increasing the number of santri through teacher professionalism at the Ihyaul Qur'an Nururrahman Wagir Malang Islamic boarding school. Result research is The transformational leadership of kyai directly has a significant influence on increasing the number of santri, with the direct influence value being 0.370 while the indirect influence value is 0.283.